The Predictive Values of Advanced Non-Small Cell Lung Cancer Patients Harboring Uncommon EGFR Mutations—The Mutation Patterns, Use of Different Generations of EGFR-TKIs, and Concurrent Genetic Alterations - Tan, Jiarong; Hu, Chengping; Deng, Pengbo; Wan, Rongjun; Cao, Liming; Li, Min; Yang, Huaping; Gu, Qihua; An, Jian; Jiang, Juan (Frontiers in Oncology, 2021)
Introduction Epidermal growth factor receptor (EGFR) 19del and L858R mutation are known as “common mutations” in non-small cell lung cancer (NSCLC) and predict sensitivities to EGFR tyrosine kinase inhibitors (TKIs), whereas 20ins and T790M mutations confer drug-resistance to EGFR-TKIs. The role of the remaining uncommon EGFR mutations remains elusive. Methods We retrospectively screened a group of NSCLC patients with uncommon EGFR mutations other than 20ins and T790M. The mutation patterns, use of different generations of EGFR-TKIs, and concurrent genetic alterations were analyzed. Meanwhile, a cohort of patients with single 19del or L858R were included for comparison. Results A total of 180/1,300 (13.8%) patients were identified. There were 102 patients with advanced or recurrent NSCLC that received first-line therapy of gefitinib/erlotinib/icotinib and afatinib and were eligible for analysis. The therapeutic outcomes among patients with common mutations (EGFRcm, n = 97), uncommon mutation plus common mutations (EGFRum+EGFRcm, n = 52), complex uncommon mutations (complex EGFRum, n = 22), and single uncommon mutations (single EGFRum, n = 28) were significantly different (ORRs: 76.3%, 61.5%, 54.5%, and 50.0%, respectively, p = 0.023; and mPFS: 13.3, 14.7, 8.1, and 6.0 months, respectively, p = 0.004). Afatinib showed superior efficacy over gefitinib/erlotinib/icotinib in EGFRcm (ORR: 81.0% vs. 75.0%, p = 0.773; mPFS: 19.1 vs. 12.0m, p = 0.036), EGFRum+EGFRcm (ORR: 100% vs. 54.5%, p = 0.017; mPFS: NE vs. 13.6m, p = 0.032), and single EGFRum (ORR: 78.6% vs. 21.4%, p = 0.007; mPFS: 10.1 vs. 3.0m, p = 0.025) groups. Comprehensive genomic profiling by Next Generation Sequencing encompassing multiple cancer-related genes was performed on 51/102 patients; the mPFS of patients without co-mutation (n = 16) and with co-mutations of tumor-suppressor genes (n = 31) and driver oncogenes (n = 4) were 31.1, 9.2, and 12.4 months, respectively (p = 0.046). TP53 mutation was the most common co-alteration and showed significantly shorter mPFS than TP53 wild-type patients (7.0 vs. 31.1m, p < 0.001). Multivariate analysis revealed that concurrent 19del/L858R and tumor-suppressor gene alterations independently predicted better and worse prognosis in patients with uncommon mutations, respectively. Conclusions Uncommon EGFR mutations constitute a highly heterogeneous subgroup of NSCLC that confer different sensitivities to EGFR-TKIs with regard to the mutation patterns. Afatinib may be a better choice for most uncommon EGFR mutations. Concurrent 19del/L858R and tumor-suppressor gene alterations, especially TP53, can be established as prognostic biomarkers.